Production Costs and Profitability for Selected Greenhouse-Grown Perennial Plants: Partial Enterprise Budgeting and Sensitivity Analysis : FE1119/FE1119, 7/2022 - Khachatryan, Hayk; Wei, Xuan (EDIS, 2022)
The purpose of this study is to present practical enterprise budgets and help growers to determine how the particular crop they are growing influences profitability. Written by Hayk Khachatryan and Xuan Wei, and published by the UF/IFAS Food and Resource Economics Department, July 2022.